An Effort for Improving 2K Students’ Learning Achievement of Hadits Subject Using Reward and Punishment Method in Gontor for Girls - Fina Miladiyati Uzma; Alinda Zakiyatul Fakhiroh (Educan : Jurnal Pendidikan Islam, 2018)
In the teaching and learning process, teachers have an important position and determinator whether or not the learning process success. The choice of appropriate learning method also need to be noticed by the teachers. Giving something new in the learning model will improve students’ spirit and achievement. One of the learning method is by implement the cooperative method which consists of  various learning methods with group system. Then, the small groups are able to build students’ togetherness and resposibility between them. This research is Classroom Action Research (CAR).  The model of Classroom Action Research chosen by the researcher is spiral model from Kemmis and Mc. Taggart. The research was done in some cycles and in every cycle consist of planning, acting, observing, and reflecting. Reward and punishment model can improve students’ learning achievement in Hadits subject for grade 2. This statement proved with the very good test result with the average passing socre 0.9% or 88%. Students study more dilligent, it is proved by students’ attitude toward the teacher while explaining the material. The students listening, pay attention, understand, memorize, and implement the materials that they learned.